Efek Moderasi Etika Auditor terhadap Hubungan Kompetensi dan Pengalaman Kerja dengan Kualitas Audit pada Kantor Akuntan Publik di Bali - Rengganis, RR. Maria Yulia Dwi; Devi, Ni Luh Nyoman Sherina; Pramanaswari, A.A. Sagung Istri; Prameswari, Ida Ayu Nirma (JURNAL ECONOMINA, 2024)
This research aims to examine the moderating effect of auditor ethics on the relationship between competency and work experience and audit quality at Public Accounting Firms in Bali. The population in this research is all Public Accounting Firms registered in the 2023 IAPI Directory, totaling 19 Public Accounting Firms with 117 auditors. The sampling technique used purposive, to obtain a sample of 72 respondents. The analysis technique used is Moderated Regression Analysis (MRA). The results of this research indicate that the variables of competence and work experience have a positive effect on audit quality, while auditor ethics are unable to moderate the influence of competence and work experience on audit quality.